Synthesis and evaluation of antibacterial activity of (R)-2-methylheptyl isonicotinate, a putative naturally occurring bioactive agent. Issue 22 (15th November 2015) - Cao, Jia; Adler, Ben; Perlmutter, Patrick
Graphical abstract: A putative antibacterial and antifungal compound, ( R )-2-methylheptyl isonicotinate, was synthesized via reductive alkylation of ( R )-4-methyldihydrofuran-2(3 H )-one. Conclusions drawn from structural characterisation data as well as bioassay results (with Bacillus subtilis or Escherichia coli ) contradict those previously reported. Abstract: A putative antibacterial and antifungal compound, ( R )-2-methylheptyl isonicotinate, was synthesized via reductive lactone alkylation of ( R )-4-methyldihydrofuran-2(3 H )-one. Structural characterisation data as well as bioassay results (with Bacillus subtilis or Escherichia coli ) contradict those previously reported.